Reestructuración técnico-administrativa en la empresa Gotittas S.A.S. en la ciudad de Bogotá D.C. (2017)
In the present degree project was to do a technical and administrative restructuring for the Gotittas S.A.S., company, with the objective to propose improvements that help the increase of the productivity and the competitiveness. In the first step, was to do a company diagnosis with the end to discover the current situation of it, using tools like the check lists of the Cámara de Comercio de Bogotá, the PESTAL Analysis and the SWOT matrix, letting to know the internal and external environment of the company.